Cost-utility analysis of PCSK9 inhibitors for hypercholesterolemia: a Chinese healthcare perspective - Hu, Dandan; Deng, Xu; Feng, Mengwen; Zhang, Xinyue; He, Qingfeng; Wang, Tao; Feng, Zhen (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the cost-utility of different dosing regimens of PCSK9 inhibitors, added to statin therapy, in patients with hypercholesterolemia or at high cardiovascular risk in China.MethodsA Markov cohort multistate-transition model was developed from the perspective of the Chinese healthcare system, with a 1-year cycle and lifetime horizon. Treatment effects were derived from a network meta-analysis. Costs, utilities, and mortality data were obtained from published literature and national databases. Both costs and outcomes were discounted at a rate of 5% annually. The primary outcome was the incremental cost-utility ratio (ICUR). The willingness-to-pay (WTP) threshold was set at 1–3 times China’s 2024 per capita gross domestic product. One-way, probabilistic, and scenario sensitivity analyses were performed to test model robustness.ResultsIn the base-case analysis, evolocumab 140 mg every 2 weeks (Q2W) was the most cost-effective option, dominating all other active regimens. Compared with statin therapy alone, it generated incremental costs of $11,109.27 and a quality-adjusted life year (QALY) gain of 0.42. The resulting ICUR was $26,217.47 per QALY, which is below the WTP threshold of $39,875.0 per QALY. Although less favorable than evolocumab, alirocumab 75 mg Q2W and tafolecimab 150 mg Q2W were also cost-effective versus statins alone, with ICURs of $34,279.73 and $34,002.10 per QALY, respectively. All other regimens were dominated, and inclisiran showed the least favorable cost-utility profile (ICUR $113,800.14 per QALY). Sensitivity analyses identified the discount rate as the key driver of uncertainty, with ICURs for evolocumab 140 mg Q2W versus statins alone ranging from $15,903.46 to $34,573.62 per QALY. Probabilistic sensitivity analysis showed a 98.9% probability of evolocumab 140 mg Q2W being cost-effective versus statins alone.ConclusionAt the current negotiated price, evolocumab 140 mg Q2W is the most cost-effective PCSK9 inhibitor regimen for Chinese patients with hypercholesterolemia or at high cardiovascular risk when added to statin therapy. Alirocumab 75 mg Q2W and tafolecimab 150 mg Q2W also represent cost-effective alternatives. These findings provide important evidence to support clinical decision-making and optimize resource allocation in China.